New Approach to the Short-Term Forecasting in the Time Series with the Structural Shock - Pavlik, Martin (Nowe podejście do prognozowania krótkoterminowego na podstawie szeregów czasowych ze zmianami strukturalnymi, 2009)
The aim is to show a new approach in the short-term forecasting in case the time series contain structural shock. Structural shock appeared in the Slovak VAT time series. The author runs ex post forecasts based on the data from January 1996-December 2006. He explored thousands of models including the transformation and compared the new research with previous research already published and logarithmised time series using logarithms with a lot of different bases. He explored bases: 5, 10, 15, 20, 25 and natural logarithm, compared the quality of the ex post forecasts and discovered that decimal logarithm was the best choice for this particular time series, the increasing number of iterations could slightly improve the forecasts and transformation was not convergent and a lot of calculation was without indicating convergence even after 250 iterations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 84, s. 94-111
Keywords: short-term forecasting; structural shocks; logarithmic function; transformation